External and internal secretion of the pancreas in experimental pancreatitis - Kuchkarova, Lyubov; ugli Kayumov, Hasan Yu; Rokhimova, Shirin; Sysa, Aliaksei (Journal of the Belarusian State University. Ecology, 2023)
Acute pancreatitis is the most widespread disease of the digestive system, the risk of exposure to which is progressively increasing worldwide. The trigger for the pathogenesis of acute pancreatitis caused by ligation of the pancreatic duct, administration of cerulin or amino acids is oxidative stress, which causes an increase in such dangerous metabolites as reactive oxygen and nitrogen species. The purpose of the study was to characterize changes in diagnostically significant indicators of pancreatic exo- and endocrine secretion in experimental acute pancreatitis caused by L-arginine in a model experiment on laboratory animals. The study was performed on outbred male rats. A model of acute pancreatitis was induced by intraperitoneal administration of L-arginine twice with an interval of 2 hours. The activity of α-amylase in the pancreatic tissue and intestinal chyme, the content of glucose, C-peptide and α-amylase activity in the blood serum of animals with experimental pancreatitis, as well as the histostructure of the pancreas were evaluated. It was established that vacuolar dystrophy, as well as edema of interacinar and interlobular connective tissue, necrosis of exocrinocytes with a violation of the structure of acini, were noted in the pancreatic tissue of animals under the influence of L-arginine. Although pancreatic islets retained their structure, however, they noticeably decreased in size. A statistically significant (1.8 times) increase in the specific activity of pancreatic α-amylase in pancreatic tissue in rats with acute pancreatitis was showncompared to control animals. The content of glucose in the blood serum of the animals of the experimental group also increased statistically significantly (by 38.5 %) compared to the control animals. The content of C-peptide in the blood of rats with induced experimental pancreatitis decreased by 68.5 %. The data obtained in this study suggest that in pancreatitis, along with dysfunction of the exocrine apparatus, symptoms of diabetes mellitus develop, which must be taken into account in the treatment of pancreatic pathologies.
Keywords: white rats; experimental pancreatitis; pancreas; α-amylase; glucose; C-peptide